The Breath of Life of Banebdjedet: Expressing an Ancient Egyptian Mortuary Belief in the Roman Period - Ortiz García, Jónatan (Gerión. Revista de Historia Antigua, 2023)
Recent studies on Osirian beliefs in the Roman period have provided access to a seemingly homogeneous religious sphere through the practices reflected in funerary assemblages, to an apparently homogeneous religious sphere, which underwent changes as a result of internal evolution itself and not only because of the cultural contacts of the time. In this context, this study presents a funerary concept involving one of the best-documented sacred animals (also in Greco-Roman literature): the Mendes ram, Banebdjedet. In the collected evidence, which are studied as a whole for the first time, this divine manifestation provides the breath of life necessary for the resurrection of the deceased. The concept is scarcely attested, but it had a relatively relevant regional spread and a significant duration